Optimization of zinc oxide surge arrester design in reducing leakage current / Nurul Ain Abdul Latiff - Nurul Ain , Abdul Latiff (2018)
A surge arrester diverts lightning surge to earth, preventing damage on electrical systems. Under normal operating condition, surge arresters do not conduct current but there is a leakage current flow across surge arresters. Leakage current is one of the factors, which contributes towards degradation of surge arresters. Numerous works on improving surge arrester designs have been conducted since the past. However, works on improvement on surge arrester design using optimisation methods are less likely to be found in literature. Therefore, improvement on surge arrester design by minimising the leakage current across the arrester using optimisation methods is proposed in this work. The main advantage of using optimisation methods is the most suitable solutions can be obtained without trial and error method, which can reduce the simulation time. A three-dimensional (3D) 11kV surge arrester model in finite element method (FEM) was developed and used to simulate the leakage current under normal operating condition. Evolutionary computation methods, imperialist competitive algorithm (ICA) and gravitational search algorithm (GSA) were employed to optimise the arrester designs, which can minimise the leakage current. Measurements of surge arrester leakage current under different conditions were also performed and were used to compare with the simulation results to validate the models that have been developed. Comparison between different optimisation methods allows the most suitable method for surge arrester design optimisation to be identified. The results from this work can also help in improving the design of surge arresters in reducing 15.63% of resistive leakage current in industries.